Early enteral feeding versus "nil by mouth" after gastrointestinal surgery: systematic review and meta-analysis of controlled trials. Issue 7316 (6th October 2001) - Lewis, Stephen J; Egger, Matthias; Sylvester, Paul A; Thomas, Steven
Abstract: Objective: To determine whether a period of starvation (nil by mouth) after gastrointestinal surgery is beneficial in terms of specific outcomes. Design: Systematic review and meta-analysis of randomised controlled trials comparing any type of enteral feeding started within 24 hours after surgery with nil by mouth management in elective gastrointestinal surgery. Three electronic databases (PubMed, Embase, and the Cochrane controlled trials register) were searched, reference lists checked, and letters requesting details of unpublished trials and data sent to pharmaceutical companies and authors of previous trials. Main outcome measures: Anastomotic dehiscence, infection of any type, wound infection, pneumonia, intra-abdominal abscess, length of hospital stay, and mortality. Results: Eleven studies with 837 patients met the inclusion criteria. In six studies patients in the intervention group were fed directly into the small bowel and in five studies patients were fed orally. Early feeding reduced the risk of any type of infection (relative risk 0.72, 95% confidence interval 0.54 to 0.98, P=0.036) and the mean length of stay in hospital (number of days reduced by 0.84, 0.36 to 1.33, P=0.001). Risk reductions were also seen for anastomotic dehiscence (0.53, 0.26 to 1.08, P=0.080), wound infection, pneumonia, intra-abdominal abscess, and mortality, but these failed to reach significance (P>0.10). The risk of vomiting was increased among patients fed early (1.27, 1.01 to 1.61, P=0.046). Conclusions: There seems to be no clear advantage to keeping patients nil by mouth after elective gastrointestinal resection. Early feeding may be of benefit. An adequately powered trial is required to confirm or refute the benefits seen in small trials.